A Prospective Study about Safety and Efficacy of Perioperative Lidocaine Infusion - Vakhtang Shoshiashvili; Ashraf El-Molla; Fawzia Aboul Fetouh; Rashed Alotaibi; Abir Kandil; Osama Shaalan; Yasser Ali (New Horizons in Medicine and Medical Research Vol. 8, 2022)
Respiratory depression, immunosuppression, muscle rigidity, negative inotropism, nausea, vomiting, hyperalgesia, urine retention, postoperative ileus, and drowsiness are all clinically significant adverse effects of opioids. Perioperative opioids are a significant contributor to the opioid epidemic in the united states and other nations. As a result, non-opioid analgesics, particularly lidocaine, are becoming more popular for perioperative use. A total of 185 adult patients were divided into two groups: control group i (105 patients) [fentanyl group] and group ii (80 patients) [opioid free anesthesia group]. Patients of both groups received at anesthetic induction: lidocaine 1.5 mg/kg bolus followed by 1.5 mg/kg/h infusion intraoperatively, and 1.5-2 mg/kg/h infusion for 2-8 hours postoperatively. Both groups received other analgesic adjuvants such as diclofenac 75 mg, paracetamol 1 gm, and mgso4 30-50 mg/kg intraoperatively. A supplemental fentanyl 1 mcg/kg was used if there is increase of mean arterial pressure (map) and/ or heart rate (hr) more than 20% above baseline. Analgesic requirements were documented following intraoperative fentanyl consumption and a visual analog scale (vas) pain score evaluation at the time of immediate recovery and after 24 hours postoperatively. Supplemental intraoperative fentanyl was needed in 8.6% of cases in group i, and in 30% of cases in group ii. Group ii also needed a higher minimum alveolar concentration (mac) of sevoflurane during first 30 minutes. Both groups needed analgesia immediately post extubation if surgeries were less than 3 hours. After 8 hours of lidocaine infusion, there was no need for additional opioids for 24 hours and only paracetamol 1 g and/or diclofenac 75 mg were enough in both groups. No significant differences in bowel function were observed between the 2 groups. Safety and efficacy of perioperative lidocaine infusion have been demonstrated. With minimal non-opioid analgesia for 24 hours, a post-operative lidocaine infusion for 5-8 hours was sufficient to ease discomfort. Opioid use during induction gives more hemodynamic stability and it is reasonable to use it in combination with lidocaine.